Synthesis and Biological Evaluation of Fluorescent Bryostatin Analogues. (25th March 2018) - Cummins, Thomas J.; Kedei, Noemi; Czikora, Agnes; Lewin, Nancy E.; Kirk, Sharon; Petersen, Mark E.; McGowan, Kevin M.; Chen, Jin‐Qiu; Luo, Xiaoling; Johnson, Randall C.; Ravichandran, Sarangan; Blumberg, Peter M.; et al.
Abstract: To investigate the cellular distribution of tumor‐promoting vs. non‐tumor‐promoting bryostatin analogues, we synthesized fluorescently labeled variants of two bryostatin derivatives that have previously shown either phorbol ester‐like or bryostatin‐like biological activity in U937 leukemia cells. These new fluorescent analogues both displayed high affinity for protein kinase C (PKC) binding and retained the basic properties of the parent unlabeled compounds in U937 assays. The fluorescent compounds showed similar patterns of intracellular distribution in cells, however; this argues against an existing hypothesis that various patterns of intracellular distribution are responsible for differences in biological activity. Upon further characterization, the fluorescent compounds revealed a slow rate of cellular uptake; correspondingly, they showed reduced activity for cellular responses that were only transient upon treatment with phorbol ester or bryostatin 1. Abstract : Bryostatin brightness : To investigate the cellular distribution of tumor‐promoting versus non‐tumor‐promoting bryostatin (Bryo) analogues, we synthesized fluorescent variants of two bryostatin derivatives that had previously shown either phorbol ester‐like or bryostatin 1‐like biological activity in U937 leukemia cells. The compounds had different biology despite their similar subcellular localization.